GUIDELINES TO DEVELOP TEACHER FOR ACTIVE LEARNING TEACHING, TAKPITTAYAKHOM SCHOOL, THE SECONDARY EDUCATIONAL SERVICE AREA OFFICE TAK - Prayoonphokkharat, Poom; Kittiratchadanon , Supaporn; Angsuchotmetee, Somchai (Journal of MCU Nakhondhat, 2024)
This research aimed to study the 1) Current condition and problem 2) Find ways and 3) Evaluate guidelines to develop teachers for active learning teaching, Takpittayakhom School, The Secondary Educational Service Area Office Tak. The mixed method was used in this research. The data sources used in this research consisted of 144 individuals, i.e., 5 school administrators, 130 teachers and 9 experts. The tools used as questionnaires and interviews. The data were analyzed by searching for percentage, frequency, mean, standard deviation and content analysis. The results of the research found that overall and desirable conditions of teacher for active learning teaching, Takpittayakhom School, The Secondary Educational Service Area Office Tak were rated at high level ( = 3.96, S.D. = 0.72). The problem of active learning teaching found that there was the most common of designing proactive learning management plan, followed by the proactive learning activities, technology media in proactive learning management and evaluation of proactive learning management, respectively. The promotion guidelines revealed that the designing proactive learning management plan, the school should train teachers to truly understand active learning teaching from expert teachers. For proactive learning activities, school should collect the digital skill of teachers to provide the development plan. The technology media in proactive learning management, school should set up learning resources and local wisdom databases. For evaluation of proactive learning management, the parent-teacher association is important to encourage the evaluation of proactive learning management. Evaluation results of the guidelines to develop teacher for active learning teaching found that the overall conditions of possibility were rated at high level ( = 4.17, S.D. = 0.24) and usefulness were rated at high level ( = 4.31, S.D. = 0.22).